Aprimoramento das propriedades do biodiesel de babaçu utilizando aditivos naturais - Girardi, Julio Cezar (2023)
The growing demand for energy combined with current environmental concerns have increasingly driven the development of biofuels. Biodiesel, which is a product derived from the transesterification of vegetable oils or animal fats, has the benefits of being non-toxic, biodegradable and providing good lubrication. However, despite the benefits for the environment, its properties as a fuel are still not ideal, presenting physicochemical characteristics that, if not controlled, damage and/or reduce engine performance. As a solution to these problems, studies have been carried out using mixtures that can improve the characteristics of biodiesel, these mixtures are diverse, among the most common are in relation to blends with diesel, use of alcohols and other biodiesels. The purpose of this work was to use a 23 factorial design on a laboratory scale in order to analyze the effect of natural additives (camphor, ethanol and peach oil/biodiesel) on the physicochemical properties of babassu biodiesel. The babassu biodiesel was characterized and later the additive mixtures were carried out following the pre-established proportions, evaluating the physicochemical properties of the additive samples according to the established norms. Two tests were carried out, test 1 with ethanol, camphor and peach oil and test 2 replacing the oil with peach biodiesel, test 2, which obtained slightly more satisfactory results with a decrease in viscosity, and a better reduction in with respect to cloud, freezing and clogging points. In the evaluation of oxidative stability, test 1 obtained the most satisfactory results. It was found in the study that camphor was the additive that best showed a tendency to be used as an additive to improve the physicochemical properties of babassu biodiesel.